PENGARUH TANAMAN STRIP TERHADAP PEMAKAIAN AIR TANAH - Syakur Syakur (Fakultas Pertanian, Universitas Syiah Kuala, 2003)
The study was conducted at the Jatikerto village, Sumber Pucung sub-district, Malang regency The Randomised Block Design was used in this experiment and each treatment was replicated twice. The study used erosion plots ( 12 x 10 ) m , with a slope of 8 % , maize ( 1 0 X 04 ) m and cassava ( 16 ) x1.0) m inter-cropped as the main crops. The plants used for the strip were gajah grass, raja grass taiwan grass, vetiver grass, benggala grass at (0.15 x 6.0) m planting distance, and Gliricidia, with seed and stump at (0.20 x 6.0) m planting distance. The result shows, soil water usage indicate that evapo-transpiration of all treatments ranged from 876 mm (4.02 mm day) to 899 mm (4.13 mim day ). There was no significant difference of soil water content at 25 cm, 50 cm and 150 cm distance from the strip but otherwise was shown by the increase of the depth of the soil